1975
DOI: 10.1017/s0003356100030403
|View full text |Cite
|
Sign up to set email alerts
|

Cereal processing and food utilization by sheep. 3. The effect of replacing whole barley by whole oats on food utilization and firmness and composition of subcutaneous fat

Abstract: 1. Forty-eight early-weaned lambs were used in an experiment in which whole barley was gradually replaced by whole oats in order to produce different types of rumen fermentation. 2. The type of rumen fermentation promoted by whole barley did not give rise to excessively soft fat in female lambs; in males, however, some carcasses were unacceptable. An increase in the proportion of propionic acid in the rumen liquor was associated with an increased proportion of odd-and branched-chain fatty acids and a decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 9 publications
2
0
0
Order By: Relevance
“…Softness was associated with adipose tissue water content and proportions of oddFA and oBCFA and anteisoFA, but was the opposite to ESFA (C 12:0 , C 14:0 , C 16:0 and C 18:0 ), as reported by Bas et al [9] and Bozzolo and BouillierOudot [12]. These relationships confirmed the conclusions of several authors who related the fat softness problem to high adipose tissue water content [4,30] and high proportions of oddFA and BCFA [9,27,36]. The relationship between SI and BCFA appeared closer with oBCFA than anteisoFA and not with isoFA, which is probably a consequence of the origin of these groups of FA.…”
Section: Fat Softnesssupporting
confidence: 84%
“…Softness was associated with adipose tissue water content and proportions of oddFA and oBCFA and anteisoFA, but was the opposite to ESFA (C 12:0 , C 14:0 , C 16:0 and C 18:0 ), as reported by Bas et al [9] and Bozzolo and BouillierOudot [12]. These relationships confirmed the conclusions of several authors who related the fat softness problem to high adipose tissue water content [4,30] and high proportions of oddFA and BCFA [9,27,36]. The relationship between SI and BCFA appeared closer with oBCFA than anteisoFA and not with isoFA, which is probably a consequence of the origin of these groups of FA.…”
Section: Fat Softnesssupporting
confidence: 84%
“…As ALA proportion had a loading score orthogonal to the PC1 axis, it confirmed that, even when lambs were fed diets rich in ALA, softer and more colored AT was directly related to high proportions of Odd-FA and OBCFA and to lower proportions of even-saturated FA. This has already been observed in lambs fed high concentrate diets (Bas, Giral, & Rouzeau, 1998;Miller, Kunsman, & Field, 1980;Normand et al, 2005;Orskov, Duncan, & Carnie, 1975).…”
Section: Effect Of Ewe Linseed Supplementation and Lamb Linseed Supplsupporting
confidence: 57%